A Phenomenological Analysis of the Parental Role in Emotional Eating of Young Obese Iranian Women - ehteram ebrahimi; Fatemeh Mohammadi Shirmahaleh; Mojtaba Habibi Asgarabad; marjan Mardani Hamooleh (Kerman University of Medical Sciences, 2021)
Introduction: Previous studies have confirmed the high prevalence of emotional eating in obese women and its relationship with weight gain. Given that eating behavior is formed since early childhood in interaction with parents, it is essential to study the parental role in obese women's emotional eating experiences. Accordingly, the present study aimed to describe and interpret the parental role in the emotional eating experiences of young obese Iranian women. Methods: The participants in this qualitative study that was conducted using a hermeneutic phenomenological approach were 17 young women with a body mass index (BMI) of 30 and above. The women were selected using purposive sampling with maximum variation. The data in this study were collected through semi-structured in-depth interviews that were conducted individually and face to face. Data analysis was performed using the seven-step analysis method proposed by Dickelman et al. Results: The main theme revealed from the data analysis was "parenting experiences". This theme was further categorized into 6 subthemes including "the insecure attachment symbol", "alleviation of psychological distress caused by parents", "misunderstanding of food as a magic parenting wand", "over-providing food security for the child", "contradiction in fostering overeating behavior with destructive blaming", and "child learning". Conclusion: The subthemes that emerged in this study reflect various dimensions of the parental role in the emotional eating of young obese Iranian women. The results of this study provide deep insights into planning psychotherapy interventions for emotional eating and weight management, especially in women.